Flow characteristics in free impinging jet reactor by particle image velocimetry (PIV) investigation. (13th July 2016) - Zhang, Jun; Liu, Youzhi; Qi, Guisheng; Jiao, Weizhou; Yuan, Zhiguo
Abstract: The flow characteristics in free impinging jet reactors (FIJRs) were investigated using particle image velocimetry (PIV). The effects of the Reynolds number ( Re ) and the ratio of jet distance to jet diameter ( w / d ) on flow behavior were discussed for equal volumetric flow rates of the two jets. The impingement plane, instantaneous velocity, mean velocity, and turbulent kinetic energy (TKE) distribution of FIJRs are measured from captured images using the PIV technique. As Re increases, the average diameter of the impingement plane linearly increases. The instability of the liquid is closely related to the jet velocity or the Re . However, the stagnation point is insensitive to the variation of the Re . The droplets break up from the turbulent liquid in the 'wall-free' environment of FIJRs, so that the liquid back-flow found in confined impinging jet reactors (CIJRs) is not observed. Increasing the Re from 1800–4100 or decreasing the w / d from 20–6 plays a similar role in increasing the TKE values and intensifying turbulence, which promotes the momentum transfer and mixing efficiency in FIJRs.